Making sense of projects: Developing project portfolio management capabilities - Frederik Ahlemann; Peder Bergan; Erik Karger; Malte Greulich; Stefan Reining (Schmalenbach Journal of Business Research (SBUR), 2024)
Project management and project portfolio management (PPM) foster competitiveness by facilitating the implementation of organizational strategy. Although organizations often struggle to develop PPM capabilities, the academic community does not have an in-depth understanding of the conditions for successfully developing these capabilities. In response, we conducted a~multiple-case study with 50~interviewees to develop a~theoretical model of the PPM capability-building process. This model is built on the notion of organizational sensemaking and identifies aspects that comprehensively explain why it usually takes so long to develop PPM capabilities. We conceptualize the PPM capability-building process as one that is strongly influenced by (1) the effects of structural rearrangements, (2) the appropriate use of external resources during that process, (3) the role of executive support and legitimization, (4) episodes of regression, and (5) the need for internalization and habitualization. In addition, we provide starting points for explaining organizational capability building in more general terms.
Keywords: M10; M14; M15; O31; O32; O33; 650; Capabilities; Capability building; External resources; Habitualization; Internalization; Interpretive schema; Legitimization; Organizational sensemaking; Project management; Project portfolio management